IOCONTROL POTENTIALS OF TRICHODERMA HARZIANUM AGAINST SCLEROTIAL FUNGI - RITESH KUMAR; SUDARSHAN MAURYA; ANJALI KUMARI; JAIPAL CHOUDHARY; BIKAS DAS; S. K. NAIK; S. KUMAR (The Bioscan, 2012)
Trichoderma species are well known antagonists which have strong bio-control potential against soilborne phytopathogenic fungi. Five potential isolates of Trichoderma hazianum were isolated from two different types of soils in which two were from alfisol (mango and litchi orchards) of the ICAR RCER Research Centre, Plandu, Ranchi, Jharkhand, India and three were from the inceptisol (Eastern Uttar Pradesh) India using Trichoderma Selective Medium (TSM) and characterized. Two alfisol (native) isolates (Th-4 and Th-5) along with three inceptisol isolates of Varanasi (Th-1, Th-2 and Th-3) were used in screening of antagonistic potential against two phyto- pathogenic sclerotial fungi Rhizoctonia solani and Sclerotium rolfsii in dual culture. Among the isolates, the local/native ones isolated from alfisol have shown potential antagonism and inhibited R. solani with percent inhibition of 46.77 and 50.34 as compared to inceptisol isolates with inhibition percentage of 22.33, 26.21 and 23.08 respectively. The alfisol isolates also showed potential antagonism against S. rolfsii with percent inhibition of 44.67 and 47.88 as compared to inceptisol isolates with inhibition percentage of 3.97, 7.97 and 28.72 respectively. Compared to inceptisol isolates, biomass accumulation and total phenol content was also reported high in the alfisol isolates.